Implementation of Contextual Learning in Improving Accounting Problem Solving Skills Balance Sheet Topics for Class XI Students at Private Vocational School Taman Siswa Medan Academic Year 2023/2024 - Samio, Samio; Hasibuan, Mhd Zulkifli; Sultoni, Dani Iskandar (Holistic Science, 2023)
This research aims to determine and analyze the improvement in problem solving abilities of class This classroom action research was carried out in 2 cycles, each cycle consisting of planning, action implementation, observation and reflection stages. The data obtained in this research include the results of observations of student activity during the learning process and giving test questions at the end of each cycle as well as the results of student reflection at the end of each lesson, the teacher's ability to manage learning taken from the teacher's observation sheet. The indicator of success in this research is that students are considered to have completed learning if they achieve a score of ? 65%, while a class is considered to have completed learning if there are 85% of students in the class who achieve an absorption capacity of ? 65%. The research results in cycle 1 showed that the percentage of student learning completeness was 75% so that the class had not finished learning and the percentage of student activity was 66.7%, while the research results in cycle 2 showed that the percentage of student learning completeness was 92.5% so the class had been completed learning and the percentage of student activity is 87.50%. From this research, it can be concluded that implementing a contextual learning approach can improve the accounting problem solving abilities of class.